Cyclicality of growth opportunities and the value of cash holdings - Ahrends, Meike; Drobetz, Wolfgang; Puhan, Tatjana Xenia (Journal of Financial Stability, 2018)
We show that business cycle dynamics and, in particular, the cyclicality of a firm’s growth opportunities, determine the value of corporate cash holdings. An additional dollar of cash is more valuable for firms with less procyclical expansion opportunities. This valuation effect is strongest for low leverage and high R&D firms, but is independent of their financial status. Corporate cash holdings provide the flexibility to invest for firms that have expansion opportunities during crisis times with business cycle downturns and supply-side financial constraints. Cash holdings in firms with less procyclical growth opportunities are associated with higher investment and better operating performance.